Defect Dynamics in MAPbI3 Polycrystalline Films: The Trapping Effect of Grain Boundaries. Issue 9 (31st August 2020) - Mattoni, Alessandro; Meloni, Simone
Abstract: Metal halide perovskites, chemical compounds of ABX3 stoichiometry (A=CH3 NH3 +, Cs +, …; B=Pb 2+, Sn 2+ ; X=I −, Br − ), have attracted great interest as they emerged as one of the most promising class of materials for low‐cost photovoltaics with over 25 % certified power conversion efficiency. An important open question for further improving their efficiency and stability is the formation and dynamics of point defects, for example, iodide vacancies and interstitials. In particular, recently it has been shown that defects strongly interact with grain boundaries, which, for example, prevents a quick restoration of initial conditions of film when kept in the dark after illumination [ Phung et al ., Adv. Energy Mater . 2020, 1903735]. It has also been shown that iodide defects may accumulate at grain boundaries, where they induce carriers' recombination [ Park et al ., ACS Energy Lett . 2019, 4, 1321–1327]. In this article, we make use of molecular dynamics and ab initio simulations to follow the evolution and compute the energetics of a iodide vacancy, V I, and an iodide Interstitial, i I ', interacting with Σ5/(102) grain boundaries of different termination, MAI and PbI2 . We show that the polarization charge of Σ5/(102) grain boundary associated to a prescribed termination drives the dynamics of charged defects, V I and i I ' . The long‐range interaction of grain boundaries with charged species might induce the accumulation of point defects present in crystallites or formed under operation conditions. Moreover, the selective attraction of specific defects by a grain boundary may help splitting Frenkel pairs formed in solar cells under illumination, thus preventing the quick annihilation of defects and enhancing the effect of light in inducing degradation processes. Abstract :